Analisis Kemampuan Pemecahan Masalah Matematik Siswa SMK di Kota Cimahi pada Materi Program Linier - Elfia Sri Rahayu; Resti Naila (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2019)
The purpose of this research is to analyze a problem solving ability of students in mathematic to finished the question of problem solving for material linear program. This research applied for students grade XI in one of vocational high school in cimahi city with the sample 29 students. The method of the research is descriptive qualitative. The instrument is question of problem solving. The result by the task of students were score and analyze the mistake of the answer. The result show is the student who can not finished the problem of understanding a problem is 6 students. Students who can not planing the strategy or transformations is 11. Student who can not finished the problem solving is 18. Student who can not conclude the answer is 23. The conclution is the problem solving ability os students in one of vocational high school in cimahi is low, then efforts need to be made to improve.